PELANGGARAN PRINSIP-PRINSIP PIAGAM PBB 1945 DALAM SERANGAN MILITER RUSIA KE WILAYAH UKRAINA - Pustika, Anna Anindita Nur Pustika; Angela Merici Vanessa S.A; Stephanie Liestia G (Penerbit Universitas Atma Jaya Yogyakarta, 2023)
In international law, an independent and sovereign state has an obligation to respect another state such as not intervening, respecting territorial integrity, and resolving international disputes peacefully. The conflict between Russia and Ukraine attracted world attention since 2014 when Russia annexed the territory of Crimea, Ukraine which made a referendum and resulted in Crimea joining Russia. In 2022, the relations between Russia and Ukraine had problem because Russia did military operations by detonating bombs on several cities in Ukraine. The action raised questions about how the general principles of international law works that every independent state should respect. This paper examines the conflict relations between Russia and Ukraine against the general principles of international law based on the 1945 UN Charter. This paper used qualitative research with normative juridical research methods. The result of this paper is that the military operation by Russia does not reflect the implementation and respect of Article 2 paragraph (4) and Article 2 paragraph (7) of the UN Charter regarding the prohibition of using armed violence and acting to intervene in other countries. Also, Russia's actions unfulfilled the self-defense criteria specified by Article 51 of the UN Charter.